Adoption of Soil Health Card by Farmers in Haryana: Perceptions, Challenges and Way Forward - Ohlan, Ramphul; Ohlan, Anshu; Singh, Rajbir (Indian Journal of Extension Education, 2025)
The Soil Health Card (SHC) program aims to enhance soil health by providing farmers with detailed information about the nutrient status of their soil. This study investigated farmers' perceptions, challenges, and potential pathways to enhance the adoption of SHC recommendations in Haryana. The analysis was based on primary data collected through face-to-face interviews with SHC adopters and non-adopters, utilizing a pre-tested semi-structured schedule in 2024. The findings revealed that farmers' perceptions of the benefits of the SHC remained low. The perceived constraints in obtaining SHC scored higher than those associated with implementing its recommendations. The study identified the annual lease land system as a key factor driving the indiscriminate use of fertilizers in the state. Although the recent reduction in the per-bag quantity of urea decreased usage in Haryana, any further reduction in bag weight might result in increased fertilizer consumption. The study recommended the use of mobile soil testing vans and timely delivery of soil health cards to promote greater adoption.